THE SIGNIFICANCE OF MODERN DIAGNOSTIC METHODS OF RABIES VIRUS IN MEDICINE - Mamatmusayeva F.Sh; Asatova N.B; Mamanov J.B (Scholar Express Journal, 2023)
In the analysis of these literatures, the pathogenesis of the rabies virus in humans in recent years (2012-2022), ways of transmission, modern diagnostic methods, widely used vaccinations, importance of serological, molecular biological, immunological methods used in treatment and diagnosis, their possibilities and advantages are presented. . For example, the Rapid Fluorescent Focus Inhibition Test (RFFIT), ELISA, viral RNA - RT-PCR, immunofluorescent test (dFAT), mouse inoculation test (MIT), as well as many clinical trials conducted on patients have shown the effectiveness of several vaccines and pharmacological agents. for example, Rabisin™, Recombitek®C6/CV, Recombitek®C8, SPBN GASGAS, SAD L16, and several immune boosters are among them
Keywords: molecular-biological; PCR; RT-PCR